Pengaruh Penggunaan Media Video Pembelajaran Terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI Kelas V SDN 07 Padang Leban Tapan - Septriani, Nola; Hendri, Nofri; Anugrah, Septriyan; Amsal, Mutiara Felicita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to see the impact of using video learning media on students' learning outcomes in the subject of PAI in grade V at SDN 07 Padang Leban. This research uses quantitative research with a quasi-experimental type to compare the learning outcomes of students in the experimental class and the control class. The sample of this research consists of students from class V.A and V.B with a total of 17 students per class. The data collection technique used objective test questions totaling 50 items. The obtained data were analyzed using homogeneity tests, normality tests, and difference tests (t-tests). The research results show that the average score of the experimental class, which is 90.82, is higher than the average score of the control class, which is 74.94. From the t-test analysis, it was obtained that t_calculated > t_table, which is 2.89 > 2.03 at a significance level of α 0.05, thus Ho is rejected and Ha is accepted. Therefore, it can be concluded that the use of learning videos has a significant effect on students' learning outcomes in the PAI subject for grade V at SDN 07 Padang Leban Tapa.